Haplotype Study in Argentinean Variegate Porphyria Patients - Granata, Bárbara Xoana (2016)
Background/Aims: The porphyrias are genetically heterogeneous diseases, and each mutation is exclusive to one or two families. Among the mutations responsible for variegate porphyria in our country, c.1042-1043insT stands out, since it was described only in Argentina and is present in about 40% of genetically diagnosed families. Thus, we hypothesized the possible existence of a common ancestor for the mutation in our population. Methods: We conducted a study based on microsatellite (short tandem repeats) haplotypes. Results: We found a common haplotype in all of the patients carrying the common mutation. The age of the mutation was estimated to be about 375 years. Conclusion: There is a recent founder effect in our population for this particular genetic alteration in variegate porphyria.